Hearing impairment in the P23H-1 retinal degeneration rat model - Sotoca, Jorge V.; Alvarado, Juan C.; Fuentes-Santamaría, Verónica; Martinez-Galan, Juan R.; Caminos, Elena (Frontiers in Neuroscience, 2014)
The transgenic P23H line 1 (P23H-1) rat expresses a variant of rhodopsin with a mutation that leads to loss of visual function. This rat strain is an experimental model usually employed to study photoreceptor degeneration. Although the mutated protein should not interfere with other sensory functions, observing severe loss of auditory reflexes in response to natural sounds led us to study auditory brain response (ABR) recording. Animals were separated into different hearing levels following the response to natural stimuli (hand clapping and kissing sounds). Of all the analyzed animals, 25.9% presented auditory loss before 50 days of age (P50) and 45% were totally deaf by P200. ABR recordings showed that all the rats had a higher hearing threshold than the control Sprague-Dawley (SD) rats, which was also higher than any other rat strains. The integrity of the central and peripheral auditory pathway was analyzed by histology and immunocytochemistry. In the cochlear nucleus (CN), statistical differences were found between SD and P23H-1 rats in VGluT1 distribution, but none were found when labeling all the CN synapses with anti-Syntaxin. This finding suggests anatomical and/or molecular abnormalities in the auditory downstream pathway. The inner ear of the hypoacusic P23H-1 rats showed several anatomical defects, including loss and disruption of hair cells and spiral ganglion neurons. All these results can explain, at least in part, how hearing impairment can occur in a high percentage of P23H-1 rats. P23H-1 rats may be considered an experimental model with visual and auditory dysfunctions in future research.